Multi-constraints based RPL objective function with adaptive stability for high traffic IoT applications - Abdelhadi Eloudrhiri Hassani; Aicha Sahel; Abdelmajid Badri; El Mourabit Ilham (Institute of Advanced Engineering and Science, 2021)
The internet of things technology is classified as a Low power and lossy network. These kinds of networks require a trustworthy routing protocol considered as the backbone for management and high quality of service achievements. IPv6 routing protocol for Low power and lossy network (RPL) was able to gain popularity compared to other routing protocols dedicated to IoT for its great flexibility through the objective function. Default objective functions implemented in the RPL core are based on a single metric. Consequently, the routing protocol can’t cope with different constraints and show congestion issues in high traffics. For that, we proposed in our paper multi-constraints-based objective function with adaptive stability (MCAS-OF), which uses novel strategies for Radio strength indicator, node energy consumption, hop count and a designed work-metric combination, new rank processing, and parent selection procedure. The network stability was also taken into account, since the multi constraints can lead to frequent parent changes, using an adaptive threshold. The proposal, evaluated under the COOJA emulator against standard-RPL and EC-OF, showed a packet delivery ratio improvement by 24% in high traffics, a decrease in the power consumption close to 44%, achieved less latency and DIO control messages, it also gives a good workload balancing by reducing the standard deviation of node’s power consumption.